IL-33 at the Crossroads of Metabolic Disorders and Immunity - Tu, Lei; Yang, Lijing (Frontiers in Endocrinology, 2019)
As a cytokine in interleukin-1(IL-1) family, interleukin-33(IL-33) usually exists in the cytoplasm and cell nucleus. When the cells are activated or damaged, IL-33 can be secreted into extracellular and regulate the functions of various immune cells through binding to its specific receptor suppression of tumorigenicity 2 (ST2). Except regulating the function of immune cells including T cells, B cells, dendritic cells (DCs), macrophages, mast cells, and innate lymphoid cells, IL-33 also plays an important role in metabolic diseases and has received an increasing attention. This review summarizes the regulation of IL-33 on different immune cells in lipid metabolism, which will help to understand the pathology of abnormal lipid metabolic diseases, such as atherosclerosis and type 2 diabetes.